The Self-Care in Chronic Obstructive Pulmonary Disease Inventory: Development and Psychometric Evaluation. Issue 1 (March 2020) - Matarese, Maria; Clari, Marco; De Marinis, Maria Grazia; Barbaranelli, Claudio; Ivziku, Dhurata; Piredda, Michela; Riegel, Barbara
This study developed two instruments, the Self-Care in Chronic Obstructive Pulmonary Disease (COPD) Inventory (SC-COPDI) and the COPD-Self-Care Self-Efficacy Scale (SCES), and tested their psychometric properties on a convenience sample of 498 patients from Northern, Central, and Southern Italy. First, the domains and the items of the SC-SCOPDI were generated based on the middle-range theory of self-care of chronic illness, comprising the dimensions of self-care maintenance, self-care monitoring, and self-care management, and the SCES-COPD was developed accordingly. Second, we assessed the content validity of each scale. Third, we conducted a multicenter cross-sectional study to test their structural validity, convergent and discriminative validity, internal consistency, and test–retest reliability. The theoretical dimensions of the two instruments were confirmed through confirmatory factor analysis. Convergent validity was demonstrated by the correlation among the three self-care scales and the Self-Efficacy Scale, and discriminative validity by higher self-care scale scores in individuals with greater COPD severity and poorer health status. The global reliability index ranged from .78 to .92 for all scales. The intraclass correlation coefficients were higher than .70. Further studies are needed to confirm the psychometric properties of the two instruments in different COPD populations and countries to extend their use in clinical practice.